Severe Influenza A(H1N1) Virus Infection Complicated by Myositis, Refractory Rhabdomyolysis, and Compartment Syndrome - Camila D. Odio; Charisse Mandimika; Thiago A. Jabuonski; Maricar Malinis (Case Reports in Medicine)
Myositis is a rare and morbid complication of influenza infection that can rapidly progress to rhabdomyolysis with acute renal failure. Here, we describe a 35-year-old obese woman with severe influenza A(H1N1) virus infection complicated by myositis, refractory rhabdomyolysis, and compartment syndrome.